2022
DOI: 10.1002/anie.202201378
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Enzyme Activity by the Modulation of Covalent Interactions in the Confined Channels of Covalent Organic Frameworks

Abstract: Controllable regulations on the enzyme conformation to optimize catalytic performance are highly desired for the immobilized biocatalysts yet remain challenging. Covalent organic frameworks (COFs) possess confined channels with finely tunable pore environment, offering a promising platform for enzyme encapsulation. Herein, we covalently immobilized the cytochrome c (Cyt c) in the size‐matched channels of COFs with different contents of anchoring site, and significant enhancement of the stability and activity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 58 publications
1
54
0
Order By: Relevance
“…Recently, Wang et al reported an enhancement in enzyme activity by modulating the covalent interactions in the confined channels of COFs. 211 By tuning the contents of the anchoring sites in the COF channels, significant activity enhancement and structural stability of the enzymes were achieved. This work demonstrated that the modulation of the covalent interactions could induce a disturbance in the enzyme conformation, resulting in the higher accessibility of the active sites of the enzymes.…”
Section: Enzyme Conformation and Its Functional Activitymentioning
confidence: 99%
“…Recently, Wang et al reported an enhancement in enzyme activity by modulating the covalent interactions in the confined channels of COFs. 211 By tuning the contents of the anchoring sites in the COF channels, significant activity enhancement and structural stability of the enzymes were achieved. This work demonstrated that the modulation of the covalent interactions could induce a disturbance in the enzyme conformation, resulting in the higher accessibility of the active sites of the enzymes.…”
Section: Enzyme Conformation and Its Functional Activitymentioning
confidence: 99%
“…The effectiveness of the covalent interaction modulation and the customizable finite pore channels of COF offer promise for developing highperformance biocatalysts. [71] In 2021, for applications in long-term starvation therapy and photodynamic therapy (PDT), Wan's group constructed an enzymatic nanocapsule based on porphyrin-based COF to load GOx and CAT (Figure 8b). This system combined starvation therapy and PDT by co-immobilizing the two enzymes, which had a better therapeutic effect than ordinary monotherapy.…”
Section: Enzyme@cofmentioning
confidence: 99%
“…This material had a long-range-ordered structure in which building blocks were controlled in 2D or 3D space to form pores with uniform diameters Reproduced with permission. [71] Copyright 2022, Wiley-VCH GmbH. b) Schematic illustration of the preparation of the nanopocket and the enzyme catalytic reactions for cancer therapy.…”
Section: Enzyme@cofmentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: zhangjun.upc@gmail.com b College of Science, China University of Petroleum, Qingdao 266000, P. R. China benefit from their atomic thickness, high density, and, uniform and adjustable pore size. [25][26][27][28] However, it has been reported that the minimum pore size in both COFs and 2D-polymers is in the range of 0.5-4.7 nm, [29][30][31][32] whereas the kinetic diameter of common gas pairs is in range of 0.25-0.4 nm, resulting in a size mismatch between the pore and the gas molecule. Recently, an ionic liquid (IL) which has a low volatility, is non-toxic, and has high chemical thermal stability, [33][34][35][36] was adopted to form 2D material supported IL membrane for CO 2 separation, and which exhibits an outstanding CO 2 separation capability, which largely surpasses most of the previously reported CO 2 separation membranes.…”
Section: Introductionmentioning
confidence: 99%